Factors Affecting Attrition Among Certified Public Accountants in Davao Del Norte - Joe Mari N. Flores; Angel Nhova P. Omalay; Devien D. Padillo; Shaine C. Romaguera (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
A gradual reduction in a company's employee count indicates attrition. Several factors influenced this incident, including employees' preferences and personal needs, environmental conditions, and workplace relations. The study identified the factors affecting attrition among Certified Public Accountants in Davao del Norte. This employed exploratory factor analysis in a non-experimental quantitative research design. A total of 132 participants were selected from a population of 197 currently employed in specific organizations within Davao del Norte. The researchers created a contextualized instrument that incorporated factors affecting attrition among CPAs. Exploratory Factor Analysis, the factor rotation method, Bartlett's Test of Sphericity, and the Kaiser-Meyer-Olkin (KMO) test are among the statistical tools used for data analysis and interpretation. Analysis revealed nine factors affecting attrition: Team performance, Job stability, Work itself, Intended-Systematic Exploration, Job preparation, Work security, Managerial support, Recognition, and Facility.